1994
DOI: 10.1016/0165-1781(94)90043-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal plasma levels of serine, methionine, and taurine in transient acute polymorphic psychosis

Abstract: The present study explored the usefulness of plasma amino acid concentrations in discriminating a subgroup of patients with transient acute polymorphic psychoses characterized by psychosensory symptoms (APP+ patients). Levels of amino acids in the plasma of APP+ patients were compared with levels in psychiatric patients with other types of psychotic symptomatology and a healthy control group. Both the APP+ patients and patients with bipolar affective disorder had significantly lower plasma concentrations of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 9 publications
0
19
0
3
Order By: Relevance
“…Glycine and serine have drawn particular attention in schizophrenia research. Some studies observed elevated plasma levels of glycine and serine in schizophrenia patients (5,64), although others could not confirm these alterations (22,47). These contradictory results may be explained by the difference of high-risk, low-risk genotypes distribution in these various schizophrenia patients' samples.…”
Section: Other Plasma Amino Acid Changesmentioning
confidence: 85%
“…Glycine and serine have drawn particular attention in schizophrenia research. Some studies observed elevated plasma levels of glycine and serine in schizophrenia patients (5,64), although others could not confirm these alterations (22,47). These contradictory results may be explained by the difference of high-risk, low-risk genotypes distribution in these various schizophrenia patients' samples.…”
Section: Other Plasma Amino Acid Changesmentioning
confidence: 85%
“…A disturbed serine metabolism in a subgroup of patients suffering from transient acute polymorphic psychoses has been described (Bruinvels and Pepplinkhuizen, 1984;Fekkes et al, 1994). These patients also showed decreased plasma levels of methionine which is suggestive of a disturbed remethylation of homocysteine.…”
Section: Introductionmentioning
confidence: 95%
“…In animal models of intrauterine infections, a decrease in hippocampal taurine levels of the foetus has been shown, supporting the causal relationship between maternal infection/inflammation during pregnancy and a higher risk for schizophrenia-related neuropathology in the adult offspring (Winter et al, 2009). In addition, altered taurine levels have been documented in patients with acute polymorphic psychosis and depression and in pathological gamblers (Fekkes et al, 1994;Nordin and Sjödin, 2006;Samuelsson et al, 2012).…”
Section: Introductionmentioning
confidence: 98%